2007
DOI: 10.1161/01.str.0000257996.26950.59
|View full text |Cite
|
Sign up to set email alerts
|

Can Faith Protect From Emotional Distress After Stroke?

Abstract: Background and Purpose-Emotional distress is common in the aftermath of stroke and can impact negatively on the outcome. The study was aimed at evaluating whether religious beliefs can protect from emotional distress. Methods-Data were collected from 132 consecutive inpatients who were hospitalized for stroke rehabilitation and met the research requirements. At admission all study participants received a semi-structured interview on religious beliefs (Royal Free Interview for religious and spiritual beliefs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 46 publications
(48 reference statements)
3
58
0
Order By: Relevance
“…Further critical evaluation is provided at the end of this section. Giaquinto et al (2007) also presented results in support of those of Robinson-Smith (2002) and in contrast to those of this study. They reported that religious beliefs were associated with lower anxiety and depression scores among Italian stroke patients (predominantly Christian).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Further critical evaluation is provided at the end of this section. Giaquinto et al (2007) also presented results in support of those of Robinson-Smith (2002) and in contrast to those of this study. They reported that religious beliefs were associated with lower anxiety and depression scores among Italian stroke patients (predominantly Christian).…”
supporting
confidence: 91%
“…Research studies appear to show a positive relationship between religious practices, such as prayer, and coping with illness and medical treatment (Kaye and Raghavan 2002). In the stroke context, limited evidence suggests that religion may help to reduce emotional distress post-stroke, although in cases where patients believe their stroke has been a punishment from God, emotional distress is increased (Giaquinto et al 2007). This finding highlights the need to assess what types of religious coping strategies patients are using and any negative coping such as denial, fatalism, or blaming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, adults who were admitted to hospital for stroke rehabilitation and who scored high in religious and spiritual beliefs endorsed lower levels of anxiety and depressive symptoms than less religious/spiritual individuals. 6 Increased spirituality in adults with non-acute traumatic brain injury was associated with positive psychological coping strategies. 7 In studies with a sample of heterogeneous adult rehabilitation patients, including individuals with spinal cord injury (SCI), increased spirituality was associated with higher levels of quality of life and increased life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Cases and controls did not however differ in their score on ocular pain and discomfort subscales (Table 3), p = 0.098; therefore, the experience of pain and discomfort was similar in both groups. The similar experience of ocular pain and discomfort subscale among cases and controls may be because of many factors which may include, but not limited to, social support that alleviates pain 31 and religious beliefs 32 that enable people to endure suffering, pain and discomfort, therefore making the experience of pain and discomfort a less contributing factor to reduced quality of life among cases. Furthermore, most causes of low vision do not have ocular pain as an associated factor.…”
Section: Vision-specific Impact Of Low Visionmentioning
confidence: 99%